PENINGKATAN HASIL BELAJAR DAN KECAKAPAN SOSIAL SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN BERBASIS MASALAH DI SDN 060843 MEDAN - Siregar, Mahrani Fitri (Jurnal Tematik, 2018)
This study aims to improve student learning outcomes and students' social skills, and the use of the Problem Based Lerning model. This research is a classroom action research. The results showed that in the first cycle the average student for the three assessments was 2.31, then in the second cycle the average student for the three assessments was. 3.20. An increase of 2.96% for the assessment of student learning outcomes. For students' social skills there is also an increase from cycle I to cycle II. The indicator of "cooperating with other friends" increased to 66.67% to 86.67%; "Controlling emotions" increased from 76.67% to 80%; "Interacting with other friends" increased from 60% to 87.67%; "Managing conflict" increased from 76.67% to 93.33%; "Tolerance" increased from 73.33% to 86.67%; "Cultivating sportsmanship and discipline" increased from 70% to 80%; "Listening to other friends" increased from 63.33% to 80%; "Communicating with other friends" increased from 73.33% to 80%; and the "lead" indicator increased from 70% to 83.33%.